Объяснение:
1. 2x-3y=-7; [*(-3)]
3x-2y=-8; [*2]
------------
-6x+9y=21; (1)
6x-4y=-16; (2)
------------------
Складываем (1) и (2)
9y-4y=21-16;
5y=5;
y=1.
-----------
Подставим в исходное:
2x-3*1=-7;
2x=-7+3;
2x=-4
x= -2.
***
2. x-3y=-4; (1)
5x-3y=-8; (2)
-----------------
Из (1) x=-4+3y;
Подставим в (2):
5(-4+3y)-3y=-8;
-20+15y-3y=-8;
15y-3y=-8+20;
12y=12;
y=1.
------------
y=1 подставим в (1)
x-3*1=-4;
x=-4+3;
x=-1.
***
3. y=3x+2 ;
y-5x=4.
-------------------
Решаем графически. Смотрите скриншот.